Evaluating the mechanical and thermal performance of high-temperature low sag (HTLS) conductors: A comparative study of ACCC, ACSS, and ACSR conductors - Pooya Parvizi; Milad Jalilian; Karl D. Dearn (Results in Engineering)
Conventional aluminium overhead conductors like ACSR suffer from severe disadvantages in high-temperature situations: high sag, thermal limits, and increased energy losses. A laboratory-based study comparing the mechanical and thermal performance of two HTLS conductors, ACCC and ACSS with conventional ACSR conductors. Experimental testing and mathematical analysis confirm ACCC has greater performance in the areas of creep resistance, superior sag-tension-temperature stability, and stress-strain behaviour. The tension loss measurement of ACCC BERN at maximum temperature reaches nearly 50 %, indicating better performance than that ACSS (58–60 %) and ACSR DOTTEREL/GA (∼74 %). Ten-year creep strain of the ACCC's composite core is approximately 0.035 % which is better than the values for ACSS and ACSR samples which are 0.041–0.060 % and 0.047 %, respectively. The stress-strain analysis confirms ACCC's core is an elastic material that resists plastic deformation under cyclic loading. Real-world deployments validate that these attributes result in 27 % more aluminium and double the ampacity without additional structural change. The thirty-year long-term price analysis positions ACCC as the lowest total cost option. The study confirms that ACCC conductors are an advanced power grid solution that addresses sag related outages and failures, and provides lower maintenance and improved upgrades to the grid. This work gives the first direct comparison of HTLS conductors using established direct tests with critical benchmark conditions and suggests guidance for utilities interested in reliability and sustainability.